A Framework for Sovereign AI Governance and Economic Growth in Cameroon - Eyong Atem (International Journal of Recent Technology and Applied Science (IJORTAS), 2026)
Artificial Intelligence is no longer just a trend in technology. It has become a structural force that determines national competitiveness and economic resilience. While many advanced nations are already integrating AI into their core systems, most Sub-Saharan African states still lack the institutional frameworks needed to turn these innovations into sustainable development. This paper argues that Cameroon should not view AI simply as modernization. Instead, it must be treated as a sovereign strategy built on institutional economics, deliberate governance, and a solid blended finance architecture. Using comparative policy analysis and digital infrastructure modeling, the study proposes a three-layer framework tailored to Cameroon’s specific political economy. This model draws on international standards from the OECD, UNESCO, and the African Union, alongside the NIST Risk Management Framework. The findings show that with coordinated reform, AI could boost Cameroon’s long-term productivity by 1.5% to 2.8% annually. To fund this transition, the paper introduces a blended finance structure designed to attract multilateral banks and private venture capital. Further research is needed to explore the longitudinal impact of these AI deployments on local labor markets and the creation of indigenous datasets that reflect Cameroon’s unique linguistic diversity. Ultimately, this work contributes to the growing body of research on digital sovereignty and the political economy of AI in frontier markets.